Prediction of biochemical cure in patients with medullary thyroid cancer. Issue 6 (28th February 2020) - Machens, A; Lorenz, K; Dralle, H
Abstract: Background: The impact of number of node metastases versus metastatic lymph node ratio versus AJCC node category on biochemical cure in medullary thyroid cancer (MTC) is not well defined. Methods: Multivariable logistic regression analysis was used to determine clinical and histopathological variables that contribute to biochemical cure in node-positive MTC. Results: Some 584 of 1026 patients with MTC underwent systematic lymph node dissections for node-positive disease; 27·4 per cent (54 of 197) were biochemically cured after the initial operation and 13·5 per cent (42 of 310 patients) after repeat surgery. Cured patients had significantly less extrathyroid extension (11–14 versus 33·2–55·6 per cent), fewer lymph node metastases (median 2–4 versus 12–16), a lower metastatic lymph node ratio (median 0·05–0·08 versus 0·23–0·28), and were less likely to have AJCC pN1b disease (56–76 versus 89·9–91·6 per cent) and distant metastases (0 versus 28·4–37·1 per cent) than patients who were not cured. Biochemical cure curves advanced steadily up to 7–12 node metastases and a metastatic lymph node ratio of 0·33, eventually levelling off after 16–17 node metastases and metastatic lymph node ratios of 0·45–0·65. In logistic regression analysis, number of lymph node metastases (odds ratio (OR) 17·24 for more than 20 metastases, OR 5·28 for 11–20 metastases, OR 2·22 for 6–10 metastases), preoperative basal serum calcitonin (OR 6·24 for over 1000 pg/ml), reoperation (OR 5·34) and extrathyroid extension (OR 2·42) independently predicted failure to reach biochemical cure. Conclusion: Number of lymph node metastases, unlike metastatic lymph node ratio or AJCC node category, determines likelihood of biochemical cure after initial and repeat surgery for node-positive MTC. Graphical Abstract: In medullary thyroid cancer, number of node metastases (odds ratio (OR) 17·24 for more than 20 metastases, OR 5·28 for 11–20 metastases, OR 2·22 for 6–10 metastases relative to 1–5 metastases), basal calcitonin (OR 6·24 for over 1000 pg/ml relative to 10–500 pg/ml), repeat surgery (OR 5·34) and extrathyroid extension (OR 2·42) independently predict failure to reach biochemical cure. Number of nodes key